Faktor yang Mempengaruhi Minat Mahasiswa Berinvestasi di Pasar Modal Syariah Melalui Galeri Investasi Iain Zawiyah Cot Kala Langsa - Haris Nandar; Mustafa Kamal Rokan; M Ridwan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
The students' interest in investing is relatively low, even though they have received knowledge related to the capital market. The purpose of this study was to determine what factors influence student interest in investing in IAIN Investment Gallery Zawiyah Cot Kala Langsa. This research is a quantitative research conducted at the Faculty of Economics and Business in Islam (FEBI) IAIN Zawiyah Cot Kala Langsa. The research sample was selected using a purposive sampling technique, namely FEBI students who had learned about the capital market since the establishment of the Investment Gallery as many as 60 students. The instrument used is a questionnaire sheet. Data is processed through the SPSS program using the t-test. The results showed that the value of t-count was 3.457 and the t-table value was 2.00 (t-count > t-table). Based on these values it can be concluded that the factors that influence student interest in investing in the Islamic capital market IAIN investment gallery stock Zawiyah Cot Kala Langsa is motivation.